The role of civil-military cooperation in contemporary United Nations peacekeeping operations: a case study of UNIFIL - Slobodan M. RADOJEVIC (Bulletin of "Carol I" National Defense University)
The paper explores the place and role of civil-military cooperation (CIMIC) in contemporary United Nations (UN) peacekeeping operations. The author’s starting point is that civil-military cooperation is important for the success of a peacekeeping operation, as the CIMIC personnel engage in the implementation of CIMIC tasks in order to create a favorable civilian environment. Through these activities, the CIMIC personnel influence the security of the unit and contribute to the success of the mission. The paper aims to advance the understanding of civil-military cooperation by clarifying how the concept is understood, shaped, and applied in  contemporary UN peacekeeping operations. With this in mind, the interview has proven to be the best research technique for obtaining information on how the CIMIC personnel understand, implement, and develop the functions of the CIMIC in UN peacekeeping operations. This section presents experiences in the application of the CIMIC in the peacekeeping operation in Lebanon (United Nations Interim Force in Lebanon – UNIFIL) as a case study. The paper emphasizes that the successful implementation of civil-military cooperation in a peacekeeping operation can affect the strategic level, i.e. exert an influence on the success of the operation itself. Emphasis is placed on presenting the range of roles and functions that the CIMIC personnel perform in peacekeeping operations under the auspices of the UN. The paper concludes that contemporary peacekeeping operations have evolved and require a significant component of civil-military cooperation.